2009
DOI: 10.1590/s1516-89132009000700019
|View full text |Cite
|
Sign up to set email alerts
|

Thermoanalytical and starch content evaluation of cassava bagasse as agro-industrial residue

Abstract: Starch nutritional fractions as well as thermal properties and other analysis are essential for food and industrial application. Cassava bagasse is an important agro-industrial residue and its starch content was evaluated using two alternative methods. Thermal characterization and microscopy analyses helped to understand how hydrolysis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0
6

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 19 publications
2
7
0
6
Order By: Relevance
“…It is also possible that the cassava starch extraction technology used in different studies has influenced the bagasse composition. The majority compounds found in the cassava bagasse included fiber, with a content of 58.19%, similar to that reported by Soccol [40], and residual starch, with a content of 41.24% (db), lower than that reported in other studies, which have found values of 66-84% (db) using enzymatic hydrolysis [8,44,48]. The fresh cassava used in the region where the Almidones de Sucre plant is located presents a starch content ranging from 53.16 to 78.88% (db) [49,50].…”
Section: Resultssupporting
confidence: 82%
“…It is also possible that the cassava starch extraction technology used in different studies has influenced the bagasse composition. The majority compounds found in the cassava bagasse included fiber, with a content of 58.19%, similar to that reported by Soccol [40], and residual starch, with a content of 41.24% (db), lower than that reported in other studies, which have found values of 66-84% (db) using enzymatic hydrolysis [8,44,48]. The fresh cassava used in the region where the Almidones de Sucre plant is located presents a starch content ranging from 53.16 to 78.88% (db) [49,50].…”
Section: Resultssupporting
confidence: 82%
“…The cassava bagasse was collected from the exit of the conveyer belt to the storage silo and packed into low-density polyethylene sacks, which were immediately transported to the laboratory. The material was dried in an oven with air circulation (Tecnal, TE-394/ 3, Piracicaba, Brazil) at 55°C for approximately 24 h (Lacerda et al, 2009). The pregelatinised flour (PGF) made from dehydrated cassava starch and bagasse (70:30), conditioned to 16 g (100 g) À1 moisture, was processed in a single screw extruder (Inbramaq,PQ 30,Ribeirão Preto,Brazil), with a screw compression rate of 3:1; a feed rate of 350 g min À1 ; a circular die with a mesh of 4 mm in diameter; temperatures of the first, second and third heating sections of 57, 70 and 90°C, respectively; and screw rotation of 250 rpm.…”
Section: Preparation Of Ingredientsmentioning
confidence: 99%
“…A entalpia entre amostras, para o evento de transição de fase, ocorreu com demanda crescente. Como comparação, estudos mostraram que a degradação por enzimas fúngicas resultou num aumento de entalpia frente ao aumento do tempo de tratamento das amostras, o que sugere um aumento do teor de cristalinidade, comparado ao inicial para as amostras em questão [11][12][13]. As curvas de TG-DTA de amido de abacate estão representadas na Figura 2 e as etapas -variação de massa, faixa de temperatura, picos e natureza térmica -são apresentadas na Tabela 2.…”
Section: Resultsunclassified
“…Os intervalos restantes referem-se à degradação de matéria orgânica (amilose e amilopectina) e formação de cinzas. Os resultados obtidos foram semelhantes aos encontrados em estudos prévios, utilizando diferentes tratamentos e amidos de variadas fontes botânicas [9,13,14].…”
Section: Resultsunclassified